Earlier IV thrombolysis and mechanical thrombectomy in acute ischemic stroke are associated with a better recanalization. Issue 1 (11th June 2019) - Nicastro, Nicolas; Eger, Antoine F; Boukrid, Iman I; Mueller, Hubertus FG; Machi, Paolo; Vargas, Maria Isabel; Poletti, Pierre-Alexandre; Platon, Alexandra; Sztajzel, Roman F
Introduction: Combined intravenous thrombolysis (IVT) and mechanical thrombectomy (MT) are the recommended treatment options for acute ischemic stroke (AIS). It is unclear whether earlier IVT and MT management can predict complete vessel recanalization. Methods: In this single-center retrospective observational study, we included 81 consecutive subjects with proximal middle cerebral artery AIS (age 70.5 ± 14.2 years, 53% female) who had both IVT and MT. We assessed recanalization after mechanical procedure according to modified thrombolysis in cerebral infarction (TICI) score as well as the National Institute of Health Stroke Scale (NIHSS) score at 24 h. Outcomes were modified Rankin Scale (mRS) at discharge, mRS at 3 months, death at 3 months, and prevalence of intracerebral hemorrhage during hospitalization. Results: Multinomial logistic regression ( χ 2 = 49.4, p = 0.0075, pseudo- R 2 = 0.26) showed that complete recanalization (TICI score = 3) was predicted by lower door-to-MT time ( p = 0.014, 95% confidence interval (CI) = −0.09 to −0.01) and lower symptoms-to-IVT time ( p = 0.045, 95% CI = −0.038 to −0.0004). An NIHSS score ≥10 at 24 h was predicted by higher baseline NIHSS ( p < 0.0001) and lower TICI score ( p = 0.009). Lower NIHSS at 24 h predicted a good outcome according to mRS at 3 months ( p = 0.006). Similarly, higher NIHSS at 24 h was a predictor of death at 3 months ( p = 0.013). Conclusions: The present study suggests that bridging therapy may improve vascular recanalization when both IVT and MT are performed earlier.